(untitled) (Journal of Bangladesh Academy of Sciences, 2010)
From the air particle (PM) collected from different locations of Dhaka city it has been found that about 30 - 50% of the PM10 mass (depending on location) is fine particles with aerodynamic diameter less than 2.2 μm, which are mainly of anthropogenic origin and predominately from transport related sources. On the other hand, due to the meteorological reason and long-range transport during the wintertime, the PM concentrations remain much higher than the Bangladesh National Ambient Air Quality Standard (NAAQS). Key words: Spatial distribution; Air particulate matter; Pollution DOI: 10.3329/jbas.v34i1.5490 Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 33-48, 2010